Clinical Presentation, MRI findings and Molecular insights in Diffuse Intrinsic Pontine Gliomas (DIPGs): A Comprehensive Review. - Gustavo Novelino Simao (Brazilian Society for Pediatric Neurosurgery, 2023)
Diffuse intrinsic pontine glioma (DIPG) is a highly aggressive and the most common brainstem tumor affecting pediatric patients, with a poor prognosis and limited treatment options. Despite extensive research, the median overall survival remains low, and current treatment mainly relies on radiotherapy. Recent discoveries of recurrent somatic mutations, particularly in histone 3 variants, have led to a reclassification of pediatric diffuse gliomas. However, the relationship between genetic alterations, imaging features, and prognosis is not yet fully understood. This review provides an overview of DIPG, including its clinical presentation, typical imaging findings (with a focus on MRI techniques), diagnostic challenges, treatment modalities, and recent advancements in molecular understanding. DIPG presents with characteristic neurological symptoms and often manifests as an expansile intra-axial mass in the pons, usually exhibiting typical MRI findings. Diffusion-weighted imaging and magnetic resonance spectroscopy can provide additional insights. Pathologically, most DIPGs are pediatric type of diffuse high-grade gliomas, with specific histological features and occasional leptomeningeal spread. Radiotherapy remains the mainstay treatment. However, clinical trials with new agents are ongoing, trying to improve outcomes for DIPG patients.